Productive Zakat and Family Economic Resilience: An Empirical Study of Female-Headed Households in the Post-Crisis Period - Mufidah Syamsuddin; Muh. Ahsan Kamil; Isman, Ainul Fatha (Journal of Islamic Economic and Business Research, 2026)
Female-headed households often face heightened economic vulnerability due to their dual role as primary income earners and family caregivers. This double burden can limit economic opportunities and weaken family economic resilience, making targeted empowerment interventions such as productive zakat particularly important. This study aims to analyze the effect of productive zakat on the post-crisis economic resilience of female-headed households and its role in strengthening the family economy. This study employed an explanatory sequential mixed-methods design. Quantitative data were collected from 100 female-headed household beneficiaries (mustahiq) of BAZNAS productive zakat programs and analyzed using SEM-PLS. Qualitative data were obtained through in-depth interviews with 10 participants and analyzed thematically to enrich the quantitative findings. The results indicate that productive zakat has a positive and significant relationship on economic resilience, encompassing variables such as Socioeconomic Status, economic self-reliance, economic empowerment, and family welfare. Furthermore, productive zakat was found to enhance resilience capacity by strengthening business adaptability, ensuring income sustainability, and fostering the creation of economic reserves. The implications of this research underscore the need to strengthen program design by scaling up interventions, providing ongoing support, and integrating market access to maximize the impact on post-crisis economic recovery.